Efeitos do laser de baixa intensidade e do Scaffold de Biosilicato® no processo de reparação óssea - Tim, Carla Roberta (2011)
Several resources have been studied in order to accelerate the process of bone repair. Among these resources, bioactive materials and low level laser therapy (LLLT) have gained prominence. Several studies suggest that both resources are able of stimulating osteoblast proliferation and osteogenesis at the fracture site, promoting a greater deposition of bone mass, which is fundamental for the consolidation process. Within this context, this project aimed to assess the effects of LLLT (_ = 830nm), with the fluencies of 120J/cm ² and scaffold Biosilicate®, used associated or not, on consolidation of induced tibial bone defects in the rats. In this study it was used 40 male Wistar rats (3 months ± 250g) divided into four groups (with 10 animals each): group control bone defect without any treatment (GC), group bone defect irradiated with LLLT 830nm (GL); group bone defect treated with implantation of scaffolds Biosilicate ® (GB); group bone defect treated with implantation of scaffolds Biosilicate ® and LLLT 830nm (GBL). The animals were submitted to laser irradiation (Ga-As-Al, 830nm, 100mW) at a single point on the bone defect for eight sessions, on alternate days. The euthanasia of animals occurred at day 15 after surgery, 24 hours after the last laser treatment session. Morphological analysis revealed that the laser group, showed better tissue organization in relation to other groups. Furthermore, morphometric analysis revealed that the irradiated animals showed a higher amount of newly formed bone compared to the other groups. The expression of COX-2 and RUNX-2/CBFA-1 were higher in GB and GBL groups. Also, biomechanical analysis revealed no statistical differences among experimental groups. From the results obtained in this study, it is possible to suggest that both treatments had osteogenic potential 15 days after surgery, but the LLLT was more effective in bone repair when compared to the biomaterials, or even when the two treatment modalities were associated.